2007
DOI: 10.1038/sj.bjc.6603642
|View full text |Cite
|
Sign up to set email alerts
|

The receptor tyrosine kinase EphB4 is overexpressed in ovarian cancer, provides survival signals and predicts poor outcome

Abstract: EphB4 is a member of the largest family of transmembrane receptor tyrosine kinases and plays critical roles in axonal pathfinding and blood vessel maturation. We wanted to determine the biological role of EphB4 in ovarian cancer. We studied the expression of EphB4 in seven normal ovarian specimens and 85 invasive ovarian carcinomas by immunohistochemistry. EphB4 expression was largely absent in normal ovarian surface epithelium, but was expressed in 86% of ovarian cancers. EphB4 expression was significantly as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
96
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(100 citation statements)
references
References 17 publications
4
96
0
Order By: Relevance
“…29,30 In our study, we demonstrated that EphrinA2 could endow the HCC cells with resistance to both basal and cytokine-induced apoptosis, thus providing a growth advantage to cancer cells, which consequently enhanced the development and progression of HCC. Because the mechanism underlying the regulation of cell survival and apoptosis by Eph/Ephrins in cancer cells remains largely unknown, 31 our study provides novel insights into this mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 In our study, we demonstrated that EphrinA2 could endow the HCC cells with resistance to both basal and cytokine-induced apoptosis, thus providing a growth advantage to cancer cells, which consequently enhanced the development and progression of HCC. Because the mechanism underlying the regulation of cell survival and apoptosis by Eph/Ephrins in cancer cells remains largely unknown, 31 our study provides novel insights into this mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…However, in recent years, Eph receptors and ephrins have been found to be integral players in cancer formation and progression (Wykosky and Debinski, 2008). Eph2A, as well as other members of the Eph receptor tyrosine kinase family, have been associated with advanced ovarian cancer and poor clinical outcome (Thaker et al, 2004;Wu et al, 2006;Kumar et al, 2007;Alam et al, 2008). On the basis of these data, we hypothesise that dasatinib, which targets SFKs as well as FAK and Eph2A, may show significant preclinical activity in ovarian cancer cells supporting its further clinical evaluation.…”
mentioning
confidence: 96%
“…Furthermore, down-regulation of EphB4 also resulted in a reduction in the microvessel density of tumours suggesting a negative effect on ephrin-B2 reverse signalling due to the absence of EphB4 [141]. The same findings were also concluded for studies in breast cancer cells [127], ovarian cancer cells [123,142], colorectal cancer cells [143] and bladder cancer cells [144]. These results were also demonstrated in murine mammary and ovarian xenograft models [15], and compared to models that over-expressed EphB4 which showed accelerated tumour progression and increased lung metastasis [145].…”
supporting
confidence: 70%
“…The sole, physiologically relevant ligand for EphB4 is ephrin-B2, a transmembrane protein expressed on the surface of certain cells, which interacts with EphB4 on adjacent cells during cell-to-cell contact. Data supports a role for EphB4-ephrin-B2 interaction in tumour angiogenesis and suggests that EphB4 positive tumour cells may preferentially attach to ephrin-B2 expressing endothelial cells during extravasation which is the process of translocation of circulating tumour cells out of blood vessels into surrounding tissues, thereby promoting metastatic spread [14][15][16][17][18][19].…”
mentioning
confidence: 99%
See 1 more Smart Citation